1981
DOI: 10.1111/j.1469-8137.1981.tb03197.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF THE ONION PLANT (ALLIUM CEPA) AND ONION TISSUE CULTURE

Abstract: SUMMARYTissue cultures of onion, differentiated into roots and shoots, were examined for total flavour precursor levels, composition of the flavour precursors and activity of the enzyme alliinase. Comparisons were made with undiflerentiated callus and with the roots and shoots of germinating seedlings and shooting bulbs.Undiflerentiated callus contained none of the major flavour precursor compound, 5-transprop-1 -enyl-i.-cysteine sulphoxide, but in the diflFerentiated tissue this compound was present in both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…High levels of PCSO in photosynthetic regions of leek leaf tissues suggest that the biosynthetic precursors to PCSO (and potentially other RCSOs) might be synthesized within or in close proximity to photosynthetic tissue but that other RCSOs respond to different physiological processes. Studies show that undifferentiated onion and garlic callus tissues had little to no free flavor precursors , whereas callus cells differentiating into shoots exhibit the typical complement of RCSOs found in the leaves of seedlings. Interestingly, callus cells grown in darkness and differentiating into root tissue exhibit mainly (+)-MCSO and only trace amounts of other flavor precursors which are found in high concentrations in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of PCSO in photosynthetic regions of leek leaf tissues suggest that the biosynthetic precursors to PCSO (and potentially other RCSOs) might be synthesized within or in close proximity to photosynthetic tissue but that other RCSOs respond to different physiological processes. Studies show that undifferentiated onion and garlic callus tissues had little to no free flavor precursors , whereas callus cells differentiating into shoots exhibit the typical complement of RCSOs found in the leaves of seedlings. Interestingly, callus cells grown in darkness and differentiating into root tissue exhibit mainly (+)-MCSO and only trace amounts of other flavor precursors which are found in high concentrations in the leaves.…”
Section: Resultsmentioning
confidence: 99%
“…In undifferentiated callus S-methyl-L-cysteine sulphoxide was present at a low concentration while the major precursor of onion flavour, S-trans-prop-l-enyl-L-cysteine was absent altogether [126,154]. But in undifferentiated roots and shoots this precursor was present again.…”
Section: Aromas -Monocotyledonsmentioning
confidence: 95%
“…Others have observed that full secondary metabolism in Allium sp. is associated with more complete differentiation to the level of roots or shoots rather than at the level of callus (Davey et al, 1974; Turnbull et al, 1981). Levels of RCSOs in whole plants are sensitive to sulfur fertility (Randle et al, 1995).…”
Section: Introductionmentioning
confidence: 99%